The Impact of Job Security on Employee Performance: The Mediating Role of Job Satisfaction in Oil and Gas Development Company Limited (OGDCL), Pakistan - Ghafar Ali; Faizan Pervaiz; Asim Raza (Social Science Review Archives, 2025)
This study explores the impact of job security on workers' job satisfaction and performance in the Oil and Gas Development Company Limited (OGDCL) in Pakistan. Using the 150 employees' survey data and performing correlation, regression, and mediation analysis, the current work explores if job security increases performance directly or through job satisfaction. The results show that job security neither significantly affects performance nor does it enhance job satisfaction directly but enhances job satisfaction to a great extent. Furthermore, job satisfaction is the mediator between job security and performance, and therefore, it implies stability only appears as improved outcomes when employees are satisfied. These findings supplement Herzberg's Two-Factor Theory, under which job security is a hygiene factor that removes dissatisfaction but on its own does not produce performance. The study contributes to the human resource knowledge base in developing countries and maintains that public sector institutions must combine job security with reward, participation, and opportunity for development in order to maximize employees' motivation and performance.